Microtasks: A Platform for Task Centered Collaboration - Gupta, Mohit; Joy, Joseph; Mehra, Krishna; Srinivasa, Gopal (2009)
We consider the class of applications that involve users working asynchronously or synchronously in small groups to complete a set of tasks. Despite wide applicability, broad adoption of these applications remains largely unrealized, due to the high cost of development and deployment. We introduce an abstraction for these applications that enables a substantial portion of application complexity to be factored out into a common infrastructure we call the Microtasks Environment. We describe the environment and its simplified programming model, and share our experiences in developing and deploying applications that are in actual use.